(untitled) - Hunt, Steven T. (San Francisco, 2007)
Contents: Introduction; What staffing assessments measure, why they work, and when to use them; Different types of staffing assessments; Evaluating the effectiveness of staffing assessments; Defining job performance and its relationship to assessments; Common criticisms of staffing assessments; Choosing among different assessment methods; Incorporating staffing assessments into the hiring process.
Keywords: Employment interviewing,Phỏng vấn việc làm